DEVELOPMENT OF LEARNING MEDIA BASED ON AN ANDROID APPLICATION AT VOCATIONAL HIGH SCHOOL 5 JAKARTA - Eriansyah, Imam Mahir; Nugraha, Hari Din; Eriansyah, Rivan (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
This research aimed to develop a suitable Android-based mobile learning application as a learning medium for milling machine techniques at Vocational High School (SMKN) 5 Jakarta and to assess the feasibility of the EduFrais application based on evaluations by material experts, media experts, and student responses. The study employed a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. Validation was conducted by one material expert and one media expert. The developed media was tested on 35 eleventh-grade students majoring in Machining Techniques at SMKN 5 Jakarta. Results showed that the EduFrais application's feasibility level, based on the material expert's assessment, scored 53.00 (96.36%), categorized as "Very Suitable" and "Very Feasible." The media expert's assessment yielded a score of 50.00 (83.33%), categorized as "Very Good" and "Very Feasible." Student responses during testing were predominantly positive, with each question receiving >70% positive responses and an overall percentage of 94.28%. This indicates that the Android-based EduFrais application is suitable for use as a learning medium in milling machine technique courses. The study concludes that the developed EduFrais application meets the feasibility criteria for implementation in the Milling Machine Techniques course at SMKN 5 Jakarta.